Monocrystalline molybdenum silicide based quantum dot superlattices grown by chemical vapor deposition. (September 2016) - Savelli, Guillaume; Silveira Stein, Sergio; Bernard-Granger, Guillaume; Faucherand, Pascal; Montès, Laurent
Abstract: This paper presents the growth of doped monocrystalline molybdenum-silicide-based quantum dot superlattices (QDSL). This is the first time that such nanostructured materials integrating molybdenum silicide nanodots have been grown. QDSL are grown by reduced pressure chemical vapor deposition (RPCVD). We present here their crystallographic structures and chemical properties, as well as the influence of the nanostructuration on their thermal and electrical properties. Particularly, it will be shown some specific characteristics for these QDSL, such as a localization of nanodots between the layers, unlike other silicide based QDSL, an accumulation of doping atoms near the nanodots, and a strong decrease of the thermal conductivity obtained thanks to the nanostructuration. Highlights: Molybdenum-based silicide Quantum Dot Superlattice is grown by industrial Chemical Vapor Deposition reactor. n-type monocrystalline structure has been elaborated. Chemical study is presented highlighting the dots formation and growth mechanisms. Electrical and thermal properties have been measured highlighting the influence of nanostructuration.